An investigation of the measurement properties of the physiotherapy therapeutic relationship measure in patients with musculoskeletal conditions. (4th March 2023) - McCabe, Erin; Roduta Roberts, Mary; Miciak, Maxi; Sun, Haowei (Linda); Gross, Douglas P.
Abstract: Purpose: The therapeutic relationship between a patient and physiotherapist has been associated with improved physiotherapy outcomes. However, there is no agreed upon measure of therapeutic relationship in physiotherapy. This paper describes a validation study of a new patient-reported measure, the Physiotherapy Therapeutic Relationship Measure (P-TREM). Methods: In this multi-site validation study, participants with musculoskeletal conditions ( n = 163) completed a survey containing the P-TREM, demographic questions, a Trust in Healthcare Providers scale, and a therapeutic relationship global rating for construct validation. We investigated item quality, internal structure using exploratory factor analysis (EFA), unidimensionality, internal consistency, and construct validity. We eliminated poor performing items to optimise the length of the P-TREM. Results: The final version of the P-TREM has 30 items. EFA suggests two domains: 'Physiotherapist role' and 'Patient role', correlation between factors was 0.71. Internal consistency was excellent. We found a low-moderate correlation between P-TREM scores and Trust in Healthcare Providers and a strong correlation between P-TREM scores and the therapeutic relationship global rating, confirming our hypotheses for convergent and concurrent validity. Conclusions: The P-TREM can be considered for use in clinical research to understand therapeutic relationship in the care of people with longstanding musculoskeletal conditions in outpatient, in-person settings.